Unsteady 2-D film-cooling effectiveness behind a single row of holes at different blowing ratios: Measurements using fast-response pressure-sensitive paint. (May 2018) - Cai, Tao; Peng, Di; Yavuzkurt, Savas; Liu, Ying Zheng
Highlights: Fast-PSP was used to measure film cooling effectiveness behind a row of holes. Unsteady behaviors due to flow internation of neighboring jets are revealed. Signatures of CRVP and horseshoe vortex are clearly recognized. Three types of film cooling effectiveness oscillations were determined. Unstable synthetic low-speed region, CRVP, and hairpin vortex were identified. Abstract: An experimental study of film cooling with one row of holes was conducted using fast-response pressure-sensitive paint (fast-PSP) and a high-resolution camera. The film-cooling effectiveness behind a single row of holes was measured for blowing ratios ( M ) ranging from 0.135 to 1.5. The main attention was focused on unsteady behavious of the film-cooling effectiveness, subjected to interaction between the neighbouring jets. Distribution of the time-averaged film-cooling effectiveness determined the jet lift-off beyond M  = 0.5, while the interaction between the neighbouring jets could be recognized at M  ≥ 1. Subsequently, the instantaneous film-cooling effectiveness and its space correlations were analysed and discussed in terms of flow structures like counter-rotating vortex pair (CRVP) and horseshoe vortex. Three types of film-cooling effectiveness oscillations were observed: for a low blowing ratio ( M  = 0.135), a strong oscillation were observed at the cooling hole area and a synchronised oscillation downstream of the hole; for moderate blowing ratios ( M  = 0.35, 0.52, 0.81), a sweep oscillation was observed downstream of the hole; for high blowing ratios ( M  = 1.0 and 1.5), an irregular oscillation was observed downstream of the hole. Further clarification of the unsteady film-cooling effectiveness coupled with the energetic flow structures was made using the proper orthogonal decomposition (POD) analysis, which showed three POD intensity spectra corresponding to different oscillating structures. The lowest blowing ratio ( M  = 0.135) showed the highest intensity level of the first-order mode (84%) and the steepest slope Spectra curve of the POD eigenvalues. The moderate blowing ratios ( M  = 0.35, 0.52 and 0.81) showed the lowest intensity levels of the first-order mode (21–28%) and the most gentle slope Spectra curve of POD eigenvalues. For high blowing ratios ( M  = 1.0 and 1.5), whether referring to the intensity of the first mode or the slope of the intensity Spectra curve, all were between the lowest and moderate blowing ratios. Finally, for three typical blowing ratios (M = 0.135, 0.35, and 1.5), the POD modes demonstrated the separate effects of an unstable synthetic low-speed region, a CRVP, and a highly developed hairpin vortex.